Domiciliary oxygen for chronic obstructive pulmonary disease - Cranston, Josephine M (Cochrane Database Syst Rev, 2005)
BACKGROUND: Domiciliary oxygen therapy has become one of the major forms of treatment for hypoxaemic chronic obstructive pulmonary disease (COPD) patients. OBJECTIVES: To determine the effect of domiciliary oxygen therapy on survival and quality of life in patients with COPD. SEARCH METHODS: Randomised controlled trials (RCTs) were identified using the Cochrane Airways Group COPD register using the search terms: home OR domiciliary AND oxygen. Searches were current as of January 2007. SELECTION CRITERIA: Any RCT in patients with hypoxaemia and COPD that compared long term domiciliary or home oxygen therapy with a control treatment. DATA COLLECTION AND ANALYSIS: Data extraction was performed independently by two reviewers. MAIN RESULTS: Six randomised controlled trials were identified. Survival data were aggregated from two trials of the treatment of nocturnal oxygen therapy in patients with mild to moderate COPD and arterial desaturation at night. Survival data was also aggregated from two trials of continuous oxygen therapy versus no oxygen therapy in mild to moderate COPD. Data could not be aggregated for the other two trials because of differences in trial design and patient selection. Nott 1980: continuous oxygen therapy versus nocturnal oxygen therapy: there was a significant improvement in mortality after 24 months (Peto odds ratio 0.45, 95% confidence interval 0.25 to 0.81). MRC 1981: domiciliary oxygen therapy versus no oxygen therapy: there was a significant improvement over five years in mortality in the group receiving oxygen therapy (Peto odds ratio 0.42, 95% confidence interval 0.18 to 0.98). In the two studies of nocturnal oxygen versus no oxygen therapy in patients with COPD and arterial desaturation at night: there was no difference in mortality between treated and non treated groups for either trial or when the trials were aggregated. In the two trials of long‐term oxygen therapy versus no oxygen therapy in COPD patients with mild to moderate hypoxaemia: there was no effect on survival for up to three years of follow up. AUTHORS' CONCLUSIONS: Long‐term home oxygen therapy improved survival in a selected group of COPD patients with severe hypoxaemia (arterial PaO(2) less than 55 mm Hg (8.0 kPa)). Home oxygen therapy did not appear to improve survival in patients with mild to moderate hypoxaemia or in those with only arterial desaturation at night.